Ideological framing in U.S. news coverage of Sochi Winter Olympic Games. Issue 1 (2nd January 2017) - Pan, Po-Lin; Lawal, Tolulope
ABSTRACT: This study used an ideological approach to examine news coverage of the Sochi Olympic Games in two U.S. mainstream newspapers – the Washington Times and New York Times . Based upon the theoretical framework of public diplomacy framing, findings suggested that the Washington Times framed the Sochi Olympics more negatively, while the New York Times used more neutral frames to report the games. Specifically, the Washington Times was more likely to point the finger at the ills of the city rather than focus on why people went to Sochi for the Olympics and repeat historical events and facts that described Sochi as an unsafe city. However, the New York Times framed the games more thematically that exhibited the issues of the terrorist attacks, suicide bombers, and disturbing violence toward the Lesbian, Gay, Bisexual, and Transgender people in Russia. Limitations and implications were also discussed.